INCREASING COMMITMENT TO ORGANIZATION THROUGH ORGANIZATIONAL JUSTICE AND GROUP COHESIVENESS (Study Using Correlation Approach and SITOREM Analysis on Private Junior High School Teachers in Tanah Sareal District, Bogor City) - Patras, Yuyun Elizabeth; Hendarman, Hendarman; Kuswendi, Uut (UNIVERSITAS PAKUAN, 2021)
Commitment to organization is determined by the extent to which organizational justice and group cohesiveness emerges and manifests within the organization. In the context of school, this is a challenge that must be used as a principle in the development and performance change for each element in school. The purpose of this study is to seek efforts to increase commitment to the organization through an assessment of the strength of the relationship between commitment to organization owned by teachers and organizational justice and group cohesiveness. This study was conducted with a quantitative approach using correlation analysis and SITOREM analysis. The research was conducted in 16 private junior high schools in Tanah Sareal district, Bogor City. The research population was 171 teachers, the research sample was 120 permanent teachers foundation the so-called Gru Tetap Yayasan (GTY). The results of this study are: 1) there is a very significant positive relationship between organizational justice and commitment to organization; 2) there is a very significant positive relationship between group cohesiveness and commitment to organization; 3) there is a very significant positive relationship between organizational justice and group cohesiveness together with commitment to organization. Efforts that need to be improved to increase commitment to the organization are: 1) honesty, 2) feasibility in obtaining resources, 3) propriety, 4) justification, 5) explanation, 6) process control, 7) intensity of members to be together and 9) loyalty towards school.